2015
DOI: 10.1161/circulationaha.115.017202
|View full text |Cite
|
Sign up to set email alerts
|

Survival Prospects and Circumstances of Death in Contemporary Adult Congenital Heart Disease Patients Under Follow-Up at a Large Tertiary Centre

Abstract: in this population. [4][5][6] Because of ongoing improvement of care, survival prospects of adults with congenital heart disease are likely to have changed over recent decades. Khairy et al 7 demonstrated that mortality in patients with congenital heart disease has shifted away from infants and toward adults, with a steady increase in age at death. The current study was designed to evaluate a contemporary ACHD cohort from a single tertiary center and attempt comparison with data from Background-Adult congenita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
267
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 514 publications
(284 citation statements)
references
References 24 publications
12
267
0
5
Order By: Relevance
“…Observing 274 patients with ACHD after HF hospitalization, the Dutch CONCOR (Congenital Corvitia) registry reported 1‐ and 3‐year mortality rates of 24% and 35%, respectively. Outcomes in tertiary ACHD centers in Canada and the United Kingdom demonstrate comparable mortality, with HF accounting for 21% and 42% of deaths, respectively 3, 23. Therefore, the in‐hospital mortality reported in this study likely underestimates mortality reported after ACHD HF hospitalization.…”
Section: Discussionmentioning
confidence: 70%
“…Observing 274 patients with ACHD after HF hospitalization, the Dutch CONCOR (Congenital Corvitia) registry reported 1‐ and 3‐year mortality rates of 24% and 35%, respectively. Outcomes in tertiary ACHD centers in Canada and the United Kingdom demonstrate comparable mortality, with HF accounting for 21% and 42% of deaths, respectively 3, 23. Therefore, the in‐hospital mortality reported in this study likely underestimates mortality reported after ACHD HF hospitalization.…”
Section: Discussionmentioning
confidence: 70%
“…66,67 Finally, pneumonia has been shown to be one of leading causes of death in adults with CHD. 16 Recurrent pneumonia in adults with CHD is discussed further in the section on infectious disease.…”
Section: Lung Prevalencementioning
confidence: 99%
“…In comparison with the general population, mortality is significantly higher in ACHD patients ( Figure 6). [67][68][69][70] Common comorbidities include heart failure, which may result from residual structural problems (eg, valvar insufficiency), the sequelae of cardiac repair (eg, ventriculotomy), or the underlying congenital lesion itself (eg, abnormal loading of systemic right ventricle), 69,[71][72][73] and progression to heart transplantation is increasingly common. 74 Arrhythmias are prevalent, resulting from congenital abnormalities, perioperative insult, and hemodynamic pathophysiology.…”
Section: Adults With Chdmentioning
confidence: 99%